Ekonomia społeczna w województwie lubuskim. Stan i perspektywy rozwoju = Social economy in the Lubuskie voivodeship. State and prospects for development - Łukowiak, Anita (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The text presents the aims and tasks of the social economy and includes analysis of its assumptions. It also presents the current status and perspectives of the development of the social economy in the Lubuskie voivodeship. Empirical material was local and regional documents related to this form of entrepreneurship. Attention was paid to the prospects and opportunities for development of this sector in the Lubuskie voivodeship, and barriers to the creation of new jobs within social entrepreneurship were also shown.
Keywords: ekonomia społeczna; podmioty ekonomii społecznej; wykluczenie społeczne; inkluzja społeczna; spółdzielnie; przedsiębiorczość; social economy; social economy entities; social exclusion; social inclusion; cooperatives; entrepreneurship